Input-output evaluation of kenaf biomass utilization for upstream supply chain optimization in agroindustry - Nunung Nurhasanah; Marimin Marimin; Machfud Machfud; Muhammad Romli (Agroindustrial Technology, University of Trunojoyo Madura, 2026)
Hibiscus cannabinus L. emerged as a promising natural fiber crop in Indonesia, offering significant value-added potential across its biomass components—bast, stem core, leaves, and seeds. This study presented a comprehensive value-added analysis along the upstream and midstream supply chain networks of the kenaf agroindustry. The research specifically focused on optimizing the upstream supply chain by evaluating the economic contribution of each biomass component and identifying opportunities for full biomass utilization. The Input-Output method from Indonesia’s Central Statistics Agency (BPS) was applied, along with a sensitivity analysis on market pricing scenarios. The results revealed that, for each hectare of cultivation, optimized utilization of kenaf components yielded an added value of IDR31,357,322 in the upstream network and IDR130,309,594 in the midstream traditional textile production. Notably, the incorporation of stem core (KCC and KCP), seed oil, and fermented leaf-based animal feed contributed to a 21.67% increase in upstream added value, alongside a 17.65% rise in farmers’ income. These findings demonstrated the potential for upstream supply chain optimization through low-tech, full biomass processing, supported Indonesia’s competitiveness as a global kenaf supplier, and highlighted the need for institutional frameworks to enable scale-up and sustainability.